Madame Prime Minister the story of Indira Gandhi - Garnett, Emmeline 1924- (Farrar, Straus & Giroux, 1967)
Biography of the first woman prime minister of India, Indira Gandhi, whose father, Jawaharlal Nehru, had governed India from its independence to his death in 1964.